1989
DOI: 10.1007/bf00133213
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on the enhancement of ischemic tolerance by intracoronary pretreatment with three calcium antagonists in pig hearts

Abstract: The effect of intracoronary (IC) pretreatment with different calcium antagonists (diltiazem, nifedipine, verapamil) on the development of infarcts was investigated in two experimental series including 35 open-chest pigs. The left anterior descending coronary artery (LAD) was distally ligated for 75 minutes (series A) or for 45 minutes (series B) and was reperfused for 24 hours. Infarct size was determined as the ratio of infarcted myocardium (tetrazolium stain) to the risk region (dye technique). In series A, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…We had experience with a dose of 1 mg verapamil given over 2 min in an earlier study on ischemia protection during PTCA [33]. The dose of 1 mg appears to be highly effective as shown in comparative studies of various calcium antagonists in animal experiments [37]. Recent studies on the hemodynamic effect of intracoronary verapamil support the selection of 1 mg as the most effective dosage to improve coronary flow and to reduce peripheral coronary resistance [38, 39].…”
Section: Discussionmentioning
confidence: 99%
“…We had experience with a dose of 1 mg verapamil given over 2 min in an earlier study on ischemia protection during PTCA [33]. The dose of 1 mg appears to be highly effective as shown in comparative studies of various calcium antagonists in animal experiments [37]. Recent studies on the hemodynamic effect of intracoronary verapamil support the selection of 1 mg as the most effective dosage to improve coronary flow and to reduce peripheral coronary resistance [38, 39].…”
Section: Discussionmentioning
confidence: 99%
“…Klein and colleagues (1989) have found that the development of infarcts were significantly delayed and the mean infarct sizes were smaller with intracoronary infusion of diltiazem, verapamil or nifedipine indicating that CCBs increase the ischemic tolerance significantly by their effects on calcium homeostasis in the setting of acute ischemia during baloon inflations at PCI.…”
Section: Discussionmentioning
confidence: 99%